Assessing the performance and learning curve of orthopaedic surgical trainees in primary total hip arthroplasty - McCulloch, RA; Howgate, D; Gibbs, VN; Palmer, A; Taylor, AH; Kendrick, BJL (Royal College of Surgeons of England, 2021)
Introduction The aims of this study were threefold: first, to review the surgical performance of trainees in our departments by reviewing postoperative radiographs and operative times; second, to investigate the effect of supervision and assistant grade on postoperative radiographs and operative times; and third, to monitor trainees over a 6-month period looking for changes in postoperative radiograph appearances and operative times to assess whether these parameters reflect a trainee’s learning curve. Methods A retrospective evaluation of a continuous series of primary hip arthroplasty procedures performed by 12 trainee orthopaedic surgeons (StR) during their arthroplasty rotation. In total, 348 primary total hip replacement (pTHR) operations were performed by StRs. Operative time, acetabular cup inclination, radiological leg length discrepancy (rLLD), femoral stem alignment (FSA) and the Barrack score for cementation were evaluated. The mean number of pTHRs performed per 6-month placement was 29 (range 15–51). Operative times were available for 292 cases and all postoperative imaging was evaluated. Results The mean operative time for StRs as first-surgeon was 84.3 minutes (range 42–174 minutes). Significant differences in operative times were observed between individual StRs. As a cohort, the operative times were not affected by the level of supervision but were significantly slower when StRs were assisted by other StRs. Significant differences in rLLD, FSA and Barrack score for cementation were observed across the cohort of StRs, although this did not change at a group or individual level between the first and second halves of the 6-month placement. Conclusions Used in isolation, postoperative radiographs and operative time are not an effective measure of the learning curve in primary hip arthroplasty, however, they may be a useful adjunct in assessing the performance of orthopaedic trainees when learning primary hip arthroplasty.